Analisis dan Perancangan Jaringan Mikrotik Load Balancing Pada Unit Laka Lantas Polresta Barelang: Analysis and Design of the Mikrotik Load Balancing Network at the Barelang Police Traffic Accident Unit - Nofri Yudi Arifin; Yulia Suryani; Hasan Bashori (Engineering and Technology International Journal, 2021)
The internet is currently growing rapidly. The need and rapid development in the use of the internet network requires a balance in the provision of internet facilities. Internet standard service is the continuity of the connectivity of the internet. Connections from the internet are required to always be maintained under any conditions, but not always connectivity will run smoothly, many obstacles or disturbances are encountered so that the connection does not run smoothly. Then backup management is needed from the continuity of the connection from the internet, so that if one connection is interrupted, there will be backups. One thing that can be done is to use a load balancing system. Based on the tests carried out in this study resulted in the optimal application of load balancing. The application of load balancing can run without changing the existing network, and make connections run more optimally if there is an increase in network traffic accidents due to the balanced distribution of connection lanes. Judging from the speed of network access, it is necessary to use a load balancing system. Where to run without changing the speed of the existing network and need to optimize the network.